Pigment Dispersion Syndrome and Pigmentary Glaucoma in an Emmetropic Young Male - Verma, Neha; Jawaid, Qamar (Nepalese Journal of Ophthalmology, 2020)
Introduction: Pigment dispersion Syndrome (PDS) is a disorder with an onset in mid–twenties. There occurs a disruption of the iris pigment epithelium and deposition of pigment granules throughout the anterior segment. The incidence of PDS is 4-8/ 100,000. This condition is more commonly seen In Caucasians and is considered to be rare in Indians. Case: A 33-year-old male presented with the complaint of headache for three months. He had normal vision in both eyes with visual acuity of 6/6.Observation: Krukenberg’s spindle, a classic sign of pigment dispersion syndrome was evident on slit-lamp examination over the posterior corneal surface. Gonioscopy revealed a heavy and uniformly pigmented trabecular meshwork. OCT (Optical Coherence Tomography) demonstrated a characteristic iris configuration in the form of a mid-peripheral posterior bowing of the iris .Retinal nerve fibre layer analysis done on OCT revealed glaucomatous thinning in the right eye and a more advanced defect in the left eye. A visual field examination revealed the field to be outside normal limits in both the eyes pointing towards a diagnosis of pigment dispersion glaucoma.Conclusion: The purpose of presenting this case is to caution the clinicians to carefully examine young emmetropes who present with Krukenberg’s spindle as it could be associated with PDS. Patients with Krukenberg’s spindle and without elevated lOP are often treated as normal. These patients must be cautioned regarding possible future consequences of the disease and counseled regarding the hereditary nature of the syndrome.